Proteomic Analysis Demonstrates a Molecular Dialog Between Trichoderma guizhouense NJAU 4742 and Cucumber ( Cucumis sativus L. ) Roots: Role in Promoting Plant Growth - Liu, Qiumei; Tang, Siyu; Meng, Xiaohui; Zhu, Han; Zhu, Yiyong; Liu, Dongyang; Shen, Qirong (Molecular plant-microbe interactions, 2021)
Trichoderma is a genus of filamentous fungi that play notable roles in stimulating plant growth after colonizing the root surface. However, the key proteins and molecular mechanisms governing this stimulation have not been completely elucidated. In this study, Trichoderma guizhouense NJAU 4742 was investigated in a hydroponic culture system after interacting with cucumber roots. The total proteins of the fungus were characterized, and the key metabolic pathways along with related genes were analyzed through proteomic and transcriptomic analyses. The roles played by the regulated proteins during the interaction between plants and NJAU 4742 were further examined. The intracellular or extracellular proteins from NJAU 4742 and extracellular proteins from cucumber were quantified, and the high-abundance proteins were determined which were primarily involved in the shikimate pathway (tryptophan, tyrosine, and phenylalanine metabolism, auxin biosynthesis, and secondary metabolite synthesis). Moreover, 15 N-KNO 3 labeling analysis indicated that NJAU 4742 had a strong ability to convert nitrogenous amino acids, nitrate, nitrile, and amines into ammonia. The auxin synthesis and ammonification metabolism pathways of NJAU 4742 significantly contributed to plant growth. The results of this study demonstrated the crucial metabolic pathways involved in the interactions between Trichoderma spp. and plants. [Formula: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .